Enhancement of Functional Ability in Supraspinatus Tendinitis Using Ultrasound and Isotonic Exercise: Case Study - Tu Lidya Ike Putri; Aurelia, Christabelle (Jurnal Fisioterapi Terapan Indonesia, 2024)
Supraspinatus tendinitis is an inflammation of the supraspinatus tendon caused by the supraspinatus muscle tendon overlapping with the caput longus bicep tendon so that friction and repetitive pressure occur over a long period of time and result in damage to the supraspinatus muscle tendon and supraspinatus tendinitis occurs. Characterized by complaints of pain around the shoulder followed by limitation of motion in the shoulder joint. The clinical question arises "can the application of ultrasound and isotonic exercise reduce pain and functional ability improvement?". To be able to answer this question, an evidence search was conducted on 3 data bases, namely Science Direct, Scopus, and Google Scholar. The keywords used were supraspinatus tendinitis, rotator cuff tendinitis, therapeutic ultrasound, concentric eccentric, and a maximum of the last 5 years. In the search, 330 articles were obtained that met the criteria. Further searching was done manually on the relevant bibliography. After searching the titles and abstracts of these articles, 32 articles were found that met the inclusion criteria. Then the search phase continued by reading the entire article and found suitable articles as many as 1 article on Scopus, 2 on Science Direct, and 2 on Google Scholar. To reduce pain, increase ROM, and increase muscle strength, patients are given exercise therapy and modality therapy. The evaluation results obtained in each evaluation are an improvement experienced by the patient and are evaluated using the Shoulder Pain And Disability Index (SPADI) parameters.